Verses for the dead - Preston, Douglas J; Child, Lincoln (New York : Grand Central Publishing, 2018)
"After an overhaul of leadership at the FBI$1 (Bs New York field office, A. X. L. Pendergast is abruptly forced to accept an unthinkable condition of continued employment: the famously rogue agent must now work with a partner. Pendergast and his new colleague, junior agent Coldmoon, are assigned to investigate a rash of killings in Miami Beach, where a bloodthirsty psychopath is cutting out the hearts of his victims and leaving them with cryptic handwritten letters at local gravestones. The graves are unconnected save in one bizarre way: all belong to women who committed suicide. But the seeming lack of connection between the old suicides and the new murders is soon the least of Pendergast$1 (Bs worries. Because as he digs deeper, he realizes the brutal new crimes may be just the tip of the iceberg: a conspiracy of death that reaches back decades."s
Keywords: Pendergast, Aloysius -- (Fictitious character) -- Fiction; Government investigators -- Fiction; Serial murder investigation -- Fiction; Miami Beach (Fla.) -- Fiction; Detective and mystery fiction; Thrillers (Fiction).